2014
DOI: 10.1177/070674371405900807
|View full text |Cite
|
Sign up to set email alerts
|

Male Inmate Profiles and Their Biological Correlates

Abstract: Objective:Borderline and antisocial personality disorders (PDs) share common clinical features (impulsivity, aggressiveness, substance use disorders [SUDs], and suicidal behaviours) that are greatly overrepresented in prison populations. These disorders have been associated biologically with testosterone and cortisol levels. However, the associations are ambiguous and the subject of controversy, perhaps because these heterogeneous disorders have been addressed as unitary constructs. A consideration of profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 72 publications
(138 reference statements)
1
9
0
9
Order By: Relevance
“…Participants may have had pre-existing traits that predisposed them to both aggression and traumatic experiences. For instance, antisocial personality traits include both impulsivity and aggressiveness (Horn et al, 2014). However, these personality traits were not quantified in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Participants may have had pre-existing traits that predisposed them to both aggression and traumatic experiences. For instance, antisocial personality traits include both impulsivity and aggressiveness (Horn et al, 2014). However, these personality traits were not quantified in our data.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding as this comorbidity is associated to several serious and problematic outcomes, including reoffending and suicide [30,32]. Offenders with BPD and co-morbid ASPD may have common biological risk factors [29], as well as similar developmental trajectories [27,28]. These offenders have difficulties regulating emotions and behavior and are likely to require additional efforts from probation officers, making identification and management of offenders with this comorbidity essential.…”
Section: Dsm-iv-tr/-5 Psychiatric Disordermentioning
confidence: 98%
“…It has recently been suggested that comorbid BPD and ASPD may represent a distinct syndrome. This pattern of comorbidity is associated with severe conduct disorder in childhood [27,28] and may share biological risk factors such as high testosterone/ cortisol ratio [29]. Indeed, compared with either BPD or ASPD alone, comorbid BPD and ASPD has been associated with increased suicide risk [30], violence and criminal behavior in community residents [27,31] as well as re-offending in forensic populations [32].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into neuroendocrine mechanisms underlying aggressive behavior have focused mainly on gonadal sex steroid hormones (e.g., testosterone, which is regulated by the hypothalamic–pituitary–gonadal axis [HPG]). As can be seen in Table , increased levels of the HPG hormone testosterone are observed in aggressive adolescents [Yu and Shi, ] and adult males convicted for crimes [Horn et al, ]. In contrast, a decreased free testosterone index has been associated with CD in girls [Table ; Pajer et al, ].…”
Section: Aggression Biochemistrymentioning
confidence: 99%